2012
DOI: 10.1371/journal.pone.0048101
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chicken Spleen Transcriptome after Infection with Salmonella enterica Serovar Enteritidis

Abstract: In this study we were interested in identification of new markers of chicken response to Salmonella Enteritidis infection. To reach this aim, gene expression in the spleens of naive chickens and those intravenously infected with S. Enteritidis with or without previous oral vaccination was determined by 454 pyrosequencing of splenic mRNA/cDNA. Forty genes with increased expression at the level of transcription were identified. The most inducible genes encoded avidin (AVD), extracellular fatty acid binding prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 39 publications
3
71
4
Order By: Relevance
“…Avidin is a nonspecific acute phase protein, a marker to inflammation and bacterial infections (Kunnas et al, 1992;Matulova et al, 2012). Avidin was significantly (P B0.05) increased in all infected chickens 6 days after Eimeria infection compared with the negative control groups and it was significantly higher (P B0.05) in positive control chickens compared with early toltrazuril-treated chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Avidin is a nonspecific acute phase protein, a marker to inflammation and bacterial infections (Kunnas et al, 1992;Matulova et al, 2012). Avidin was significantly (P B0.05) increased in all infected chickens 6 days after Eimeria infection compared with the negative control groups and it was significantly higher (P B0.05) in positive control chickens compared with early toltrazuril-treated chickens.…”
Section: Discussionmentioning
confidence: 99%
“…In total, nearly half (247) of the human common host response genes were present in the complete dataset. Chicken cecum transcriptome profile during innate immune response [53, 54] shared upregulation of IL8, SAA, avidin (AVID) and protein MRP-126 (M126) with the current study.
Figure 3 Gene ontology classification of differentially regulated transcripts. Biological process gene ontology (GO) terms of the annotated transcripts with absolute fold change >2, Baggerley's test P-value <0.01 (420 genes).
…”
Section: Resultsmentioning
confidence: 70%
“…Immunomodulatory role of protein M126 is an expected finding, considering that other members of S100 calgranulin family proteins have known antimicrobial anti-inflammatory roles [58] and the protein is upregulated in chicken cecum after bacterial infection [54]. Similarly, upregulation of GAL2, AVID, SAA and LY75 can be expected, based on some avian immune stimulation studies [53, 61, 78] and our general knowledge about the functions of these proteins reviewed in [5557, 62]. However the roles of AVID and SAA in avian immunity remain unclear, supposedly together having an anti-inflammatory role by suppressing cell proliferation and supplying host cells with nutrients [53, 79].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, gene expression profiling studies of murine macrophages and microglial cells have identified immunoresponsive gene 1 (Irg1) as one of the most highly up-regulated genes under proinflammatory conditions, such as bacterial infections (5)(6)(7)(8)(9). Increased Irg1 expression levels have also been detected in chicken spleen macrophages after infection with Salmonella enterica (10). Furthermore, it has been shown that IRG1 could play an important role in the susceptibility toward Marek disease virus (11).…”
mentioning
confidence: 99%